Passive and active, predator and prey: using acoustics to study interactions between cetaceans and forage fish. (23rd February 2016) - Lawrence, Joshua M.; Armstrong, Eric; Gordon, Jonathan; Lusseau, Susan Mærsk; Fernandes, Paul G.
Abstract: Fisheries acoustics surveys provide platforms for deploying passive acoustic equipment to detect cetacean vocalizations. Passive acoustic methods are developing as viable alternatives to visual surveys, particularly for small, inconspicuous species such as the harbour porpoise ( Phocoena phocoena ). Passive acoustic monitoring using a towed hydrophone array was carried out during an acoustic survey of clupeids in the Clyde Sea and surrounding sea lochs to identify spatial relationships between porpoises and their prey. Methods were developed to process passive acoustic data, successfully identifying porpoise echolocation clicks while discriminating them from the transmitted 120-kHz echosounder pulse and its reflections. To date, this has been a confounding factor which has made these survey techniques potentially incompatible. The highest biomass of pelagic fish was detected in the northernmost parts of the survey region, as were the largest number of porpoises. A moving average was used to examine the scale of the relationships identified, and it was found that while porpoises show no significant preferences for pelagic prey numbers at the smallest scales, they do show significant avoidance of larger areas (5+ km) with very low pelagic fish biomass. This study demonstrates that high-frequency passive acoustic monitoring can be used effectively alongside multifrequency fisheries echosounder surveys to provide novel insights into the trophic interactions between these species, and that further work will hopefully prove useful in improving the efficacy of management strategies for harbour porpoises.